Towards Inclusive Higher Education: Challenges and Opportunities of Artificial Intelligence in Addressing the Digital Divide - Cedeño Salazar, Pedro Antonio (2025)
The crisis brought about by the COVID-19 pandemic has exacerbated existing inequalities in access to education and technology, directly affecting vulnerable social groups and rural areas. Over 190 countries closed their educational institutions, revealing significant disparities in educational quality and access to technological resources. The lack of digital infrastructure and skills in using technology has limited the continuity of the teaching-learning process for many educators and students, highlighting the need for inclusive public policies that ensure equitable access. Artificial Intelligence (AI) emerged as a highly potential tool to improve educational access, but its implementation must consider existing inequalities. Despite technological advancements in various countries, digital divides continue to widen, particularly in Latin America, where wealth concentration and dependence on foreign technology significantly hinder local development. Strengthening connectivity and promoting digital literacy are essential to ensure that all students have equitable opportunities in an increasingly digitalized environment driven by globalization. The objective of this review article is to analyze the challenges and opportunities that artificial intelligence offers in higher education, focusing on its potential to address and reduce the digital divide exacerbated by the COVID-19 pandemic. It seeks to explore how AI can be implemented as a tool to enhance access to education and ensure a quality teaching-learning process.